Credible witness companions, prophets, hosts and other Australian mission models - Cronshaw, Darren (Springvale, VIC Urban Neighbours of Hope, 2006)
Contents : Spiritual companions for the journey -- Chaplains for convicts -- Shepherds for settlers -- Advocates for the marginalised -- Servants for the needy -- Hosts for a multicultural community -- conclusion -- Appendix: Australian theology. Includes bibliographical references and index.
Keywords: Mission of the church -- Australia -- history; Church work -- Australia -- history; Spirituality -- Australia -- history; Aboriginal Australians -- religion -- history